2015
DOI: 10.2217/bmm.15.50
|View full text |Cite
|
Sign up to set email alerts
|

Development and Regulatory Application of Microrna Biomarkers

Abstract: MicroRNAs, a class of regulatory small non-coding RNAs, are emerging as promising biomarkers for different health outcomes. Due to their tissue specificity, stability in extracellular space and high conservation between preclinical test species, applications of novel miRNA-based biomarkers for drug safety testing regarding hepatotoxicity and cardiotoxicity are investigated. Furthermore, miRNA expression is altered by environmental exposure such as cigarette smoke or polychlorinated biphenyls. As a consequence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 102 publications
0
16
0
Order By: Relevance
“…MicroRNAs (miRNAs) are short (20‐25 nucleotides), noncoding RNAs that play imperative roles in various developmental and physiological processes . Previous studies have indicated that tissue miRNA expression profiles can be considered as diagnostic biomarkers for cancer . However, this diagnostic method is limited by its invasiveness and inconvenience .…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are short (20‐25 nucleotides), noncoding RNAs that play imperative roles in various developmental and physiological processes . Previous studies have indicated that tissue miRNA expression profiles can be considered as diagnostic biomarkers for cancer . However, this diagnostic method is limited by its invasiveness and inconvenience .…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are endogenous non-coding RNAs, which play vital roles in tumor development and tumorigenesis (8)(9)(10). In some human cancers, miRNAs are often unregulated and have an oncogenic function, while most miRNAs are downregulated and may possess a tumor-suppressive activity (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…were generated using Next Generation Sequencing technology, enabling reliable quantification of in particular low‐abundance miRNAs. Circulating miRNAs were found to be stable even under conditions as harsh as boiling, extreme pH, long‐time storage at room temperature, and multiple freeze‐thaw cycles . Details regarding sample collection, sample preparation, sequencing, and data processing can be found in Krauskopf et al ., and see for patient characteristics and levels of liver damage markers.…”
Section: Methodsmentioning
confidence: 99%